Flight Control Design for Rudder Failure Event on Cessna 172 Aircraft - Zuhri, Muhammad Rizki (Indonesian Journal of Aerospace, 2025)
The Cessna 172, a widely used small commercial aircraft, is renowned for its stabilityin both longitudinal and lateral-directional dimensions. Despite its intrinsic stability, arobust control system is essential to mitigate potential failures, such as rudder malfunctions.This study developed and simulated a control system for the Cessna 172 underrudder failure conditions, relying solely on aileron input for heading control. Using a linearstate-space approach implemented in Matlab/Simulink, the control system incorporatedyaw damping, roll damping, and heading hold for stability and waypoint tracking. Initialsimulations showed that the controller could guide the aircraft to the destination waypointbut exhibited significant deviations of up to 20% under constant rudder inputs. Controllermodification to the PID controller significantly improved performance, reducing deviationsto a maximum of only 0.1% for ±5° rudder input. These results demonstrate the effectivenessof the proposed control system in compensating for rudder failure, though slightoscillations observed at the start of the trajectory suggest the need for further refinement.This research underscores the potential for adaptive and unconventional control methodsto enhance safety and reliability in small aircraft operations.